Degradation of magnesium-ion battery anodes by galvanic replacement reaction in all-phenyl complex electrolyte. (June 2019) - Wang, Zeyu; Bandyopadhyay, Arkamita; Kumar, Hemant; Li, Manni; Venkatakrishnan, Akshaya; Shenoy, Vivek B.; Detsi, Eric
Highlights: The spontaneous degradation of metallic Mg and Mg2Sn in APC has been studied using DFT calculation and experimental methods. Mg atoms from metallic Mg and Mg2Sn are oxidized by the anions present in APC through galvanic replacement reaction. APC-induced spontaneous degradation of Mg and Mg alloys is susceptible to affect the performance of Mg-ion battery anodes. Abstract: In this work, experimental and computational methods based on density functional theory (DFT) were used to study the spontaneous degradation (i.e. in the absence of any external electromotive force) of pure metallic magnesium (Mg) and magnesium stannide (Mg2 Sn) in all-phenyl complex (APC) electrolyte, a commonly used Mg-ion battery electrolyte. Our results reveal that Mg atoms can be stripped from metallic Mg and from Mg2 Sn through galvanic replacement reactions involving anions present in APC such as Ph4 Al ˉ, Ph2 AlCl2 ˉ, PhAlCl3 ˉ and AlCl4 ˉ, resulting in Mg dissolution and metallic aluminum deposition. Such a spontaneous degradation phenomenon is susceptible to impact the performance of Mg-ion battery cells in which metallic Mg or magnesium alloys are used as anodes. In particular, we have found that Mg-ion battery half-cells assembled using Mg2 Sn and metallic Mg as the working and counter electrodes, respectively, and APC as the electrolyte, exhibit Coulombic efficiencies higher than 100% at low C-rates. Such an unusual Coulombic efficiency is attributed to unbalance charge associated with the difference in Mg atoms dissolution rate between the Mg2 Sn working electrode and the Mg metal counter electrode, when these electrodes undergo spontaneous degradation in APC.